In-Silico Design of Thiadiazole Derivatives as Anticonvulsant Agents - V, Vani; Nafiya, Fathimathul; A, Harshad; M M, Mahima Krishnan; N, Naisam; Saji, Sneha (Asian Journal of Pharmaceutical Research and Development, 2024)
This study focuses on the in-silico design and molecular docking of thiadiazole and its derivatives to evaluate their potential as anticonvulsant agents.Thiadiazoles are heterocyclic compounds known for their diverse biological activities, including anticonvulsant properties.The molecular structures were subjected to various in-silico screening methods to predict their drug-like properties and pharmacokinetic profiles. Molecular docking studies were performed to assess the binding affinity and interactions of the designed compounds with key targets associated with anticonvulsant activity, particularly the voltage-gated sodium channels and GABA receptors.The docking results revealed that several thiadiazole derivatives exhibited strong binding affinities towards the targeted proteins, with favourable binding energies and significant interactions at the active sites.